In-situ research on formation mechanisms of transfer films of a Polyimide-MoS2 composite in vacuum. (February 2023) - Hu, Hanjun; He, Ying; Wang, Qihua; Tao, Liming
Abstract: For Polyimide-MoS2 composite, the friction properties were studied by a ball on disk tribometer. With regard to the scars and tracks, the evolution of morphological and chemical characteristics under different lubrication stages were comprehensively analyzed by in-situ characterizations, including XPS, SEM and Laser Scanning Profilometer. The results indicated that the formation of transfer film was intimately related with the accumulation of debris. Once the debris on ball has been accumulated enough, some of the debris containing MoS2 particles will be instantly dragged into the friction interface to form the second transfer film, which results in the appearance of 'sliding boots' and causes the instant transition of friction coefficient from the increase to the decrease.